2018
DOI: 10.1038/s41598-018-23915-0
|View full text |Cite
|
Sign up to set email alerts
|

Shared neural correlates for building phrases in signed and spoken language

Abstract: Research on the mental representation of human language has convincingly shown that sign languages are structured similarly to spoken languages. However, whether the same neurobiology underlies the online construction of complex linguistic structures in sign and speech remains unknown. To investigate this question with maximally controlled stimuli, we studied the production of minimal two-word phrases in sign and speech. Signers and speakers viewed the same pictures during magnetoencephalography recording and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 49 publications
(59 reference statements)
4
41
0
2
Order By: Relevance
“…Relating to the domain generality question above, a large meta-analysis of haemodynamic studies on conceptual processing found that ATL activity is more likely to be left lateralized when the input is a word [55]. This somewhat converges with our inability to engage the LATL without words [24,25,53]. (iv) Function as informed by connectivity.…”
Section: (B) Open Questionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Relating to the domain generality question above, a large meta-analysis of haemodynamic studies on conceptual processing found that ATL activity is more likely to be left lateralized when the input is a word [55]. This somewhat converges with our inability to engage the LATL without words [24,25,53]. (iv) Function as informed by connectivity.…”
Section: (B) Open Questionsmentioning
confidence: 90%
“…As regards generalizability of the combinatory effect in the LATL, we have shown that it occurs in reading [14,26], listening [17] and language production [18], suggesting a rather modality independent function. Crosslinguistically, the LATL effect generalizes not only to languages that are typologically far from English, like Arabic [27], but also to American Sign Language [25], which in addition uses a different articulator. Across constructions, we know that the effect obtains not only for noun phrases but also for verb phrases [27,28] and noun-noun compounds [29,30].…”
Section: Step 2: Distinguishing Between Large Classes Of Hypotheses (mentioning
confidence: 98%
“…Regarding basic semantic composition, most evidence for the ATL as the key region of conceptual combination is derived from Magnetoencephalography (MEG) studies. Increased activity in the bilateral ATL has been shown for two-word phrases as compared to single words in both the visual and auditory modality (Bemis & Pylkkänen, 2013b) and in different languages, including English, Spanish, Arabic, and American Sign Language (Bemis & Pylkkänen, 2011;Blanco-Elorrieta et al, 2018;Molinaro et al, 2015;M. Westerlund et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These two processes, though conceptually different, have been localized to similar brain regions in the left temporal lobe. For example, a minimal adjective-noun phrase such as "red boat" elicits increased activity in the left anterior temporal lobe (LATL) compared to non-compositional word lists such as "cup, boat" 1,2 , and a similar effect has been observed for a language with the reverse word order 3 and for American Sign Language 4 , suggesting a role of the LATL in conceptual combination 5 . However, the LATL is also activated when forming arbitrary associations between pairs of words such as "ring" and "cheese" 6 , and shows greater oscillatory responses for word pairs with stronger associations 7,8 .…”
Section: Introductionmentioning
confidence: 78%